Leadership of Adult Education and Family Literacy Organizations in an Era of Diminishing Resources - Merlissa C. Alfred; Mary V. Alfred (Adult Education Research Conference, 2014)
Adult education and family literacy providers must increasingly operate with diminishing resources. This research study explored how program and organization leadership navigated these environmental changes in an effort to continue meeting the needs of adults and families.